COMPARISON OF PROXIMATE COMPOSITION, PHYTOCHEMICAL CONTENTS, ANTIOXIDANT CAPACITY AND POLYPHENOLS IN BROSIMUM ALICASTRUM LEAF AND FRUIT TISSUES. - J. C. Canto-Pinto; N. I. Pat-Moreno; V. M. Moo-Huchin; E. Pérez-Pacheco; A. J. Chay-Canul; R. J. Estrada-León; E. Sauri-Duch; C. R. Ríos-Soberanis (Journal of Animal and Plant Sciences, 2024)
Breadnut Brosimum alicastrum is known to contain bioactive compounds and has been used for medicinal and food purposes for millennia. A comparison was made between the proximal chemical composition, phytochemical content, in vitro antioxidant capacity and individual phenolic compounds in B. alicastrum leaf, seed, seed coat and fruit peel. Patterns were recognized using canonical discriminant analysis. After freeze-drying, proximate analyses were done. Leaf had the highest ash, lipid and protein contents, seed coat had high crude fiber content and seeds high carbohydrates content. Ethanol:water extraction produced the highest (P≤0.05) yield in fruit peel (33.13%). Phytochemical screening revealed abundant terpenes and tannins in leaf tissue, and abundant sterols in seed coat. Total phenolic content (TPC) was highest (P≤0.05) in seeds (19.74 mg gallic acid equivalent GAE/g) and total flavonoids content (TFC) was highest (P≤0.05) in leaves (16.62 mg quercetin equivalent QE/g). The highest DPPH antioxidant capacity was identified in seed coat and the highest reducing power (RP) in leaf and fruit peel. Individual phenolic compounds concentration varied between the tissues, with leaves having the highest caffeic acid and ellagic acid contents. Linear discriminant analysis (LDA) effectively differentiated the samples by tissue. Proximal chemical composition and bioactive compounds contents differed between B. alicastrum tissues, but they all contain bioactive compounds with antioxidant potential, highlighting their potential applications in industrial systems.
Keywords: antioxidants; phytochemicals; plant-extracts; Ramón